Oligonucleotide Length‐Dependent Formation of Virus‐Like Particles. Issue 29 (27th April 2018) - Maassen, Stan J.; de Ruiter, Mark V.; Lindhoud, Saskia; Cornelissen, Jeroen J. L. M.
Abstract: Understanding the assembly pathway of viruses can contribute to creating monodisperse virus‐based materials. In this study, the cowpea chlorotic mottle virus (CCMV) is used to determine the interactions between the capsid proteins of viruses and their cargo. The assembly of the capsid proteins in the presence of different lengths of short, single‐stranded (ss) DNA is studied at neutral pH, at which the protein–protein interactions are weak. Chromatography, electrophoresis, microscopy, and light scattering data show that the assembly efficiency and speed of the particles increase with increasing length of oligonucleotides. The minimal length required for assembly under the conditions used herein is 14 nucleotides. Assembly of particles containing such short strands of ssDNA can take almost a month. This slow assembly process enabled the study of intermediate states, which confirmed a low cooperative assembly for CCMV and allowed for further expansion of current assembly theories. Abstract : Testing the limits : The formation of cowpea chlorotic mottle virus based virus‐like particles is templated by short oligonucleotides at neutral pH. A minimum length required for the well‐defined protein assembly has been found (see figure), and increased understanding of the interactions important in the assembly of viruses.